Expressão do sistema interleucina 1 (il-1) em folículos ovarianos bovinos e efeitos in vitro da il-1β na ativação de folículos primordiais. - Passos, José Renato de Sousa (2015)
This study aims to investigate the expression of interleukin 1 system (proteins and mRNA of ligands and receptors) and its distribution in ovaries of cyclic cows, as well as to evaluate the effects of IL-1β on the survival and activation of primordial follicles in vitro. The ovaries were processed for localization of interleukin 1 system in preantral and antral follicles by immunohistochemical, qPCR and western blot analysis. For in vitro studies, ovarian fragments were cultured in α-MEM+ supplemented with IL-1β (0, 1, 10, 50 or 100 ng/mL), and aftes 6 days the tissues cultured were processed for histological analysis. Immunohistochemical results showed that the proteins for interleukin 1 system (IL-1β, IL- 1RA, IL-1RI and IL-1RII) were detected in the various follicular compartments. Unfortunately, IL-1α antibodies tested did not react in bovine ovaries. All the proteins tested were observed in the cytoplasm of oocytes and granulosa cells from all follicular categories, and theca cells of antral follicles, with the exception that IL-1α has not been found in any analyzed cell. Variable levels of mRNA for the interleukin 1 system in the follicular size and classes analysed. After 6 days of culture, the presence of IL-1β (10 or 50 ng/mL) was effective in maintaining the percentage of normal follicles and in promoting primordial follicle activation. In conclusion, interleukin 1 system is differentially expressed in the ovarian cells according to the stage of follicular development. Moreover, IL-1β promotes the development of primordial follicles. These results suggest an important role of the interleukin 1 system in the regulation of folliculogenesis in bovine species.